Serum concentrations of human insulin-like growth factor-1 and levels of insulin-like growth factor-binding protein-5 in patients with nonalcoholic fatty liver disease: association with liver histology - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Objective In this study, we aimed to investigate the relationship between the histological features of nonalcoholic fatty liver disease (NAFLD) and serum insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-binding protein-5 (IGFBP-5) to determine the usefulness of this relationship in clinical practice. Materials and methods Serum samples were collected from 92 patients with biopsy-proven NAFLD and 51 healthy controls and serum levels of IGF-1 and IGFBP-5 were assayed by enzyme-linked immunosorbent assay. Result Serum IGFBP-5 levels were correlated with liver steatosis, fibrosis, and nonalcoholic steatohepatitis scores. IGF-1 levels were significantly decreased in patients with moderate-to-severe fibrosis compared with patients with no or mild fibrosis. Conclusion Serum IGFBP-5 levels may be useful to differentiate both advanced fibrosis and definite nonalcoholic steatohepatitis from other NAFLD groups. Also, serum IGF-1 levels may be useful to differentiate advanced fibrosis in patients with NAFLD. Eur J Gastroenterol Hepatol 24:255-261 (C) 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: fatty liver; insulin-like growth factor-I; insulin-like growth factor binding protein-5; NECROSIS-FACTOR-ALPHA; IGF-I; HEPATOCELLULAR-CARCINOMA; HEPATOCYTE APOPTOSIS; CELLULAR SENESCENCE; PULMONARY-FIBROSIS; METABOLIC SYNDROME; SIMPLE STEATOSIS; STEATOHEPATITIS; POPULATION